Multi criteria decision making methods for urban greenway: The case of Aksaray, Turkey - Balta, Münevver Özge; Yenil, Havva Ülgen (Land use policy, 2019)
•Greenway planning is an important component of the open and green space system to ensure urban sustainability.•AHP method provides a systematic approach to the definition of sustainable greenways.•Greenways have been incorporated in urban areas for sustainability, functionality, transportation and accessibility. Greenway planning is a key component of the open and green space system to ensure urban sustainability. Greenway planning should be included in the multi-criteria decision-making process because it involves more than one criterion and is a subject that requires the perspectives of different disciplines. The greenway based studies have become important in recent years however the sustainability-based studies on how to identify and function greenway routes in a city are quite limited. This study is to determine the sustainable and optimum greenway routes in Aksaray city in Turkey using the Analytic Hierarchy Process. The present study can play crucial role for providing sustainable planning, design and management of greenways and guiding decision makers.